2008
DOI: 10.1080/17453670810016623
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene acetabular wear in hip prostheses: Computer-simulated quantification of error caused by changes in pelvic orientation and direction of wear

Abstract: Background and purpose Polyethylene is commonly employed for bearings in acetabular cups used in hip replacements. Assessment of in vivo wear is important for evaluation and monitoring of wear in individual patients, as well as in different implant designs. Polyethylene wear is quantified by comparisons of radiographic measurements made on sequential pelvic radiographs. Variations in pelvic orientation and variation in direction of wear may cause underestimation of polyethylene wear measurements. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…A true wear penetration of 0.4 mm, for instance, would be reduced by approximately 0.02 mm (same settings as above), which is below the accuracy of the best radiographic wear measurement systems. 26 In their theoretical study of a standard cup, Foss et al 8 also concluded that wear measurement errors caused by changes in pelvis orientation were likely to be small compared to other error sources. Notably, though, they did not determine wear from two, sequential displacement vectors (reference and follow-up) using the duo-radiographic technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A true wear penetration of 0.4 mm, for instance, would be reduced by approximately 0.02 mm (same settings as above), which is below the accuracy of the best radiographic wear measurement systems. 26 In their theoretical study of a standard cup, Foss et al 8 also concluded that wear measurement errors caused by changes in pelvis orientation were likely to be small compared to other error sources. Notably, though, they did not determine wear from two, sequential displacement vectors (reference and follow-up) using the duo-radiographic technique.…”
Section: Discussionmentioning
confidence: 99%
“…Using a computer generated ‘virtual radiographic laboratory’, Foss et al 8 studied the effects of variations in pelvis orientation on the virtual wear measurement of an acetabular cup and concluded that measurement errors were likely to be small. Most modern measurement systems use the duo-radiographic wear measurement technique 9,10 in which wear is determined by comparing the two-dimensional (2D) displacement vector (usually between the cup and head centres) on a follow-up radiograph to that on a reference (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy and precision of clinical PE wear estimates depend on several variables, including patient factors (Schmalzried and Huk 2004), radiographic quality (Sychterz et al 2001), assumptions of linear wear patterns (Yamaguchi et al 1999), hip angulations (Collier et al 2003, Foss et al 2008), the wear analysis method used (Bragdon et al 2006a), intraobserver variance (Engh, Jr. et al 2002), and manufacturing tolerances of acetabular components (Hui et al 2003). Plain AP radiographs used for wear analysis are not calibrated (position coordinates), and in retrospective studies radiographs are often not obtained according to a standardized protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Plain AP radiographs used for wear analysis are not calibrated (position coordinates), and in retrospective studies radiographs are often not obtained according to a standardized protocol. The clinical positioning of patients with the risk of slight changes in hip angulations between radiographic follow-ups has been shown experimentally to influence wear results (Collier et al 2003, Foss et al 2008). The greater the change in angulations between follow-ups, the larger the magnitude of wear measured (Collier et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation